The Hermeneutics of Qur’anic Translation into Sign Language: A Study of Inclusive Pedagogy by the Qur’an Indonesia Project - Saifullah, Muhammad; Nurjanah, Ratna Aryati (Jurnal Studi Ilmu-ilmu Al-Qur’an dan Hadis, 2024)
This study investigates the implementation of inclusive Qur’anic pedagogy by the Qur’an Indonesia Project (QIP), with a focus on its Sign Language translation initiative and inclusive teaching methods. QIP, in collaboration with The Little Hijabi Home Schooling, has launched QuranIDprojectISYARAT, a digital-based endeavor aiming to improve access to the Qur’an and its translations, especially for individuals with disabilities. The QuranIDProjectISYARAT program, developed by QIP, targets the deaf community and provides Qur’anic education through platforms like Instagram and YouTube, utilizing audio, visuals, and Sign Language demonstrations. While QIP utilizes Arabic Sign Language for Qur’an translation, their interpretive process prioritizes understanding Qur’anic meanings over morphemes. This study delves into QIP’s Qur’an translation process and inclusive teaching practices, particularly focusing on the experiences of deaf or hearing-impaired individuals. By employing a netnography approach and conducting interviews with QIP’s YouTube viewers, the research investigates interactions within QIP’s online platforms and gathers insights into viewers’ perspectives. The findings suggest that QIP’s Qur’an translation incorporates Arabic Sign Language and volunteers’ interpretations or improvisations of verses, fostering comprehension and a sense of inclusion among learners in their online Qur’anic education initiatives.